COMPOSITION AND MICROSTRUCTURE OF MAGMA BODIES FROM EFFECTIVE MEDIUM THEORY - Taylor M.A.J.; Singh S.C. (My University, 2002)
The extent and seismic properties of magma bodies beneath the subsurface are normally ascertained via seismic methods. The seismic properties of such bodies depend on the composition and microstructure of both melt and crystals. Using effective medium theory, we assess the effect of microstructure, geometry and orientation of melt and crystals on the seismic properties, namely P - and S -wave velocities and anisotropy. We find that S -wave velocity and anisotropy are key observables in determining the composition and microstructure of magma bodies.
Keywords: COMPOSITION; EFFECTIVE MEDIUM; INCLUSIONS; MAGMA BODIES; MICROSTRUCTURE; SEISMIC PROPERTIES